In vivo visualization of aromatase in animals and humans - Biegon, Anat (Front Neuroendocrinol, 2015)
Aromatase catalyzes the last and obligatory step in the biosynthesis of estrogens across species. In vivo visualization of aromatase can be performed using positron emission tomography (PET) with radiolabeled aromatase inhibitors such as [(11)C]vorozole. PET studies in rats, monkeys and healthy human subjects demonstrate widespread but heterogeneous aromatase availability in brain and body, which appears to be regulated in a species, sex and region-specific manner. Thus, aromatase availability is high in brain amygdala and in ovaries of all species examined to date, with males demonstrating higher levels than females in all comparable organs. However, the highest concentrations of aromatase in the human brain are found in specific nuclei of the thalamus while the highest levels in rats and monkeys are found in the amygdala. Regional brain aromatase availability is increased by androgens and inhibited by nicotine. Future studies may improve diagnosis and treatment in brain disorders and cancers overexpressing aromatase.